Metal–Oleate Complex-Derived Bimetallic Oxides Nanoparticles Encapsulated in 3D Graphene Networks as Anodes for Efficient Lithium Storage with Pseudocapacitance - Cao, Yingying; Geng, Kaiming; Geng, Hongbo; Ang, Huixiang; Pei, Jie; Liu, Yayuan; Cao, Xueqin; Zheng, Junwei; Gu, Hongwei (Nano-Micro Letters, 2019)
In this manuscript, we have demonstrated the delicate design and synthesis of bimetallic oxides nanoparticles derived from metal–oleate complex embedded in 3D graphene networks (MnO/CoMn2O4 ⊂ GN), as an anode material for lithium ion batteries. The novel synthesis of the MnO/CoMn2O4 ⊂ GN consists of thermal decomposition of metal–oleate complex containing cobalt and manganese metals and oleate ligand, forming bimetallic oxides nanoparticles, followed by a self-assembly route with reduced graphene oxides. The MnO/CoMn2O4 ⊂ GN composite, with a unique architecture of bimetallic oxides nanoparticles encapsulated in 3D graphene networks, rationally integrates several benefits including shortening the diffusion path of Li+ ions, improving electrical conductivity and mitigating volume variation during cycling. Studies show that the electrochemical reaction processes of MnO/CoMn2O4 ⊂ GN electrodes are dominated by the pseudocapacitive behavior, leading to fast Li+ charge/discharge reactions. As a result, the MnO/CoMn2O4 ⊂ GN manifests high initial specific capacity, stable cycling performance, and excellent rate capability. Highlights: 1 Bimetallic oxides nanoparticles derived from metal–oleate complexes embedded in 3D graphene networks were fabricated by a facile and rational design approach. 2 The unique porous architecture promotes charge transfer so as to enhance the reversible capacity. 3 The synergetic effect between the 0D nanoparticles and 3D graphene networks plays an essential role in the superb electrochemical performance.